2021
DOI: 10.1186/s43162-021-00035-2
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 gene polymorphism (-1562 C/T) and its correlation with diabetic nephropathy

Abstract: Background Matrix metalloproteinase 9 (MMP-9) is an important inflammatory marker in diabetic nephropathy. Many studies assessed the association between MMP-9 gene polymorphism and different microvascular complications of type 2 diabetes mellitus, though the results were inconclusive and need further exploration. Our study aimed to assess the association between MMP-9 -1562C/T gene polymorphism and diabetic nephropathy in patients with type 2 diabetes mellitus. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
2
2
Order By: Relevance
“…However, our findings are in conflict with previous studies showing that DN affects both male and female sex equally 42 and remains stable among age groups 70 . Other studies have reported that patients with nephropathy have higher hypertension and HbA1c level, as well as dyslipidemia caused by renal injury 71,72 . This discrepancy with our results is explained by the use of antihypertensive and anti‐glycemic drugs by our patients and also by the comparable BMI between the DWN and DN groups 73 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our findings are in conflict with previous studies showing that DN affects both male and female sex equally 42 and remains stable among age groups 70 . Other studies have reported that patients with nephropathy have higher hypertension and HbA1c level, as well as dyslipidemia caused by renal injury 71,72 . This discrepancy with our results is explained by the use of antihypertensive and anti‐glycemic drugs by our patients and also by the comparable BMI between the DWN and DN groups 73 …”
Section: Discussioncontrasting
confidence: 99%
“…70 Other studies have reported that patients with nephropathy have higher hypertension and HbA1c level, as well as dyslipidemia caused by renal injury. 71,72 This discrepancy with our results is explained by the use of antihypertensive and anti-glycemic drugs by our patients and also by the comparable BMI between the DWN and DN groups. 73 The allelic and genetic association of the À790T/G variant with the risk of development of multiple diseases has been previously reported.…”
Section: Discussioncontrasting
confidence: 97%
“…For example, the T allele has been related with a lower risk of developing diabetic nephropathy in Han Chinese (16). Similarly, Shalaby et al, argued that the T allele has a protective role for the development of (17). In a study investigating the relationship between diabetic foot ulcer and MMP9 profile in T2DM patients, it was observed that MMP9 expression level increased as the wound grade increased.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies regarding the association of MMP gene polymorphism and DN provide conflicting results. Some show that certain polymorphisms of MMP-9 may be predictive factors in the development of diabetic nephropathy [30] and some suggest the protective role of the T allele SNP -1562C>T of MMP-9 against diabetic nephropathy [31,32]. It has also been shown that MMP-2 gene polymorphism is associated with susceptibility and disease progression of DN [33].…”
Section: Introductionmentioning
confidence: 99%